A composite proton exchange membrane and its preparation method and application
By using proton conductors composed of niobium iodolate HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2 in medium and high temperature proton exchange membrane fuel cells, the phosphoric acid loss problem is solved, high proton conductivity and stable operation are achieved, and the performance of the fuel cell is improved.
Patent Information
- Application Number
- CN202211401008.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-11-09
AI Technical Summary
The existing medium and high temperature proton exchange membrane fuel cells have phosphoric acid loss problems at high temperatures, resulting in a decrease in current density and poor battery operation stability.
A proton conductor composed of niobium iodolate HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2 is used, and combined with polyaryl polymers as the matrix, the strong interaction between the hydrogen bond network in niobium iodolate HNbO(IO3)4 and the inorganic oxide is formed to form a highly ordered electrolyte structure, which improves the proton conduction performance and reduces phosphoric acid loss.
It achieves high proton conductivity and strong phosphoric acid retention capability in the range of 100 to 200°C, ensuring stable operation of fuel cells at medium and high temperatures, and improving the overall performance of the cells.
Smart Images

Figure BDA0003934977150000101
Abstract
Description
Technical Field
[0001] The invention relates to a composite proton exchange membrane and a preparation method and application thereof, belonging to the technical field of new energy fuel cells. Background Art
[0002] Hydrogen energy is a renewable and clean energy source that will gradually replace increasingly depleted fossil energy and become an important part of the world's energy landscape. Fuel cells can convert hydrogen energy into electrical energy, and therefore have attracted widespread attention. Proton exchange membrane fuel cells with proton exchange membrane as electrolyte have the characteristics of high energy conversion efficiency, low operating temperature, fast startup, and long life. They can be widely used as power sources for vehicles and fixed power stations. They are currently the fuel cells with the most promising commercial applications. The proton exchange membrane is the core component of the proton exchange membrane fuel cell. While providing a one-way transmission channel for protons, it also plays a role in isolating the fuel and oxidant on both sides. Its performance directly determines the overall performance of the battery.
[0003] Perfluorosulfonic acid type proton exchange membrane is widely used due to its high proton conductivity and chemical stability. In particular, the Nafion series membrane developed by DuPont in the United States has been commercialized. However, Nafion limits the operating temperature of proton exchange membrane fuel cells to below 100°C. The lower temperature makes the battery reaction kinetics slower, the utilization efficiency of the Pt catalyst is reduced, and the Pt catalyst is easily poisoned by CO, and the battery's water and heat management system is relatively complex. The above problems can be overcome when the operating temperature of the fuel cell is increased to above 100°C. However, too high a temperature (above 500°C) will place more stringent requirements on the component materials of the proton exchange membrane fuel cell. Therefore, it is of great significance to develop medium and high temperature (100-500°C) proton exchange membrane fuel cells.
[0004] In view of the unique advantages of medium and high temperature proton exchange membrane fuel cells, research on medium and high temperature fuel cells has become a hot topic. Among them, phosphate-based proton exchange membranes have attracted widespread attention due to their good proton conductivity, but the loss of phosphoric acid has been difficult to overcome. According to literature reports, after 125 minutes of operation, the phosphoric acid-doped organic blend membrane battery loses phosphoric acid from the membrane due to the water produced, and the current density is only about 60% of the initial [Journal of New Materials for Electrochemical Systems, 2000, 3: 343-347]; another recent study also showed that after the phosphoric acid membrane runs at 150°C for 636 hours, its output power will decay to 7.6% of the initial state [Fuel Cells, 2010, 10: 299-311]. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a composite proton exchange membrane and a preparation method thereof, which are mainly used in medium and high temperature (100-200°C) fuel cells. The composite proton exchange membrane is composed of a proton conductor, a polymer matrix and phosphoric acid, with a proton conductor as an inorganic additive component and a polyaryl polymer as a matrix. The proton conductor is composed of iodinated niobium HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2.
[0006] In iodine niobium oxide HNbO(IO3)4, niobium ions coordinate with iodine groups and oxygen anions to form an overall negatively charged framework, and hydrogen protons diffuse effectively between oxygen anions and the terminal oxygen atoms of iodine groups. Therefore, iodine niobium oxide HNbO(IO3)4 has its own hydrogen bond network. It self-assembles into a highly ordered electrolyte structure with inorganic oxides. The inorganic oxide crystal size is at the nanometer level, which can provide abundant surface area. It plays the role of carrier and skeleton while having strong interaction with iodine niobium oxide HNbO(IO3)4, which can enrich the hydrogen bond network and promote proton conduction. In addition, the introduction of BPO4 further improves the proton conduction performance of the material. Therefore, the proton conductor composed of iodine niobium oxide HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2 itself has a strong proton conduction ability. At the same time, the inorganic oxide MO2 in the proton conductor of the present invention has a small crystal size and a large specific surface area, and is a better water-retaining and acid-retaining material. Introducing it into the polymer can not only appropriately improve the proton conductivity, but also reduce the loss of phosphoric acid and improve the operating stability of the battery.
[0007] The present invention provides a composite proton exchange membrane, which is composed of a proton conductor, a polymer matrix and phosphoric acid. The proton conductor is composed of iodinated niobium HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2.
[0008] Furthermore, the inorganic oxide MO2 is one or two of SiO2, TiO2 or ZrO2, and the crystal size of the inorganic oxide MO2 is 100-500nm; the mass ratio of the iodic acid niobium oxyoxide HNbO(IO3)4 to the inorganic oxide MO2 is 1:(2-15); the mass ratio of the boron phosphate BPO4 to the sum of the iodic acid niobium oxyoxide HNbO(IO3)4 and the inorganic oxide MO2 is 1:(2.5-25).
[0009] Furthermore, the polymer matrix includes one of polysulfone, polyetheretherketone, polyimide, polybenzimidazole, and polyphenylene sulfide sulfone.
[0010] Furthermore, the mass ratio of the proton conductor to the polymer matrix is 1:(5-20).
[0011] The present invention also provides a method for preparing a composite proton exchange membrane, comprising the following steps:
[0012] (1) 0.4-0.9 mmol of niobium pentoxide is mixed with 3-8 ml of hydrofluoric acid with a mass fraction of 40%, heated to 100-140° C. to dissolve, ammonia water is added to adjust the pH to 5-7, iodic acid is added, sealed, and statically treated at 150-180° C. for 48-72 hours. The static treatment mentioned in the present application means leaving it alone without any other treatment; the obtained product is filtered, washed, dried, and calcined at 400-600° C. for 4-12 hours to obtain iodinated niobium HNbO(IO3)4;
[0013] 1 g of iodinated niobium HNbO(IO3)4 is added to 2-10 g of water, stirred for 30-60 minutes, then an inorganic oxide precursor and a surfactant are added and mixed, and the mixture is stirred for 30-60 minutes, sealed, and statically treated at 80-140° C. for 6-18 hours; the obtained product is filtered, washed, dried, and calcined at 400-600° C. for 6-18 hours to obtain a mixture of iodinated niobium HNbO(IO3)4 and oxide MO2, which is recorded as NbM;
[0014] Mix phosphoric acid and boric acid (molar ratio 2:1) solutions, heat to 220-280° C., and obtain a boron phosphate precursor; calcine the boron phosphate precursor at high temperature to obtain BPO4;
[0015] Adding boron phosphate BPO4 to 0.5-2 g of water and mixing with NbM by ball milling to obtain the proton conductor;
[0016] (2) mixing the proton conductor with a polymer matrix solution to form a membrane;
[0017] (3) The membrane is immersed in phosphoric acid to obtain a composite proton exchange membrane.
[0018] Furthermore, the temperature of high temperature calcination of the boron phosphate precursor is 300-600° C. and the time is 2-24 hours.
[0019] Furthermore, the inorganic oxide precursor includes one or two of tetraethyl orthosilicate, ethyl titanate, butyl titanate, tetraethoxysilane, and ethyl zirconate, the surfactant includes any one of F127, P123, and CTAB, and the mass ratio of the inorganic oxide precursor to the surfactant is (5-15):3.
[0020] Furthermore, in step (2), the proton conductor and the polymer matrix solution are formed into a film by a casting method.
[0021] Furthermore, the proton conductor is mixed with a polymer matrix solution to obtain a mixture, the mixture is ultrasonically treated for 2 to 4 hours to obtain a membrane-forming solution, the membrane-forming solution is placed on a glass plate and dried at 55 to 65° C. to obtain the membrane; the concentration of the polymer matrix solution is 2.5 to 5% by mass.
[0022] Furthermore, in the step (3), the membrane is immersed in phosphoric acid at a temperature of 60 to 100° C. and for a time of 2 to 4 days.
[0023] The present invention also provides an application of a composite proton exchange membrane, characterized in that it is applied in a fuel cell at a temperature of 100-200°C.
[0024] The composite proton exchange membrane has a high proton conductivity at 100-200°C and a strong phosphate retention capacity, and the battery based on the membrane assembly can also operate stably at 100-200°C.
[0025] Compared with the prior art, the composite proton exchange membrane provided by the present invention has the following advantages: the proton conductor composed of iodine niobium HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2 is used as the inorganic additive component, and the polyaryl polymer is used as the matrix. The iodine niobium HNbO(IO3)4 has its own hydrogen bond network, and self-assembles with the inorganic oxide into a highly ordered electrolyte structure. The inorganic oxide crystal size is at the nanometer level, which can provide abundant surface area. While acting as a carrier and skeleton, it has a strong interaction with the iodine niobium HNbO(IO3)4, which can enrich the hydrogen bond network and promote proton conduction. In addition, the introduction of BPO4 further improves the proton conduction performance of the material. Therefore, the proton conductor composed of iodine niobium HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2 itself has a strong proton conduction ability. At the same time, the inorganic oxide MO2 in the proton conductor of the present invention has a small crystal size and a large specific surface area, and is a better water-retaining and acid-retaining material. Introducing it into the polymer can not only appropriately improve the proton conductivity, but also reduce the loss of phosphoric acid and improve the operating stability of the battery. The resulting composite proton exchange membrane is extremely dense and has a strong proton conductivity. DETAILED DESCRIPTION
[0026] The present application is described in detail below in conjunction with embodiments, but the present application is not limited to the following embodiments.
[0027] Example 1
[0028] 1) Niobium pentoxide (0.6 mmol) and hydrofluoric acid (40% by mass, 4 ml) are mixed, heated to 100°C and stirred continuously until dissolved, and ammonia water is added to adjust the pH to 6; 10 ml of 1 mol / L iodic acid aqueous solution is added, sealed, and statically treated at 150°C for 60 hours; the obtained product is filtered, washed, dried, calcined at 400°C for 12 hours, and ground into a uniform powder to obtain iodinated niobium HNbO(IO3)4. 1 g of iodinated niobium HNbO(IO3)4 is added to water, stirred evenly, and then 15 g of tetraethyl orthosilicate TEOS and 3 g of surfactant P123 are added, stirring is continued for 30 minutes, sealed, and statically treated at 120°C for 12 hours; the obtained product is filtered, washed, dried, calcined at 400°C for 18 hours to obtain a mixture of iodinated niobium HNbO(IO3)4 and silicon dioxide SiO2, which is recorded as NbSi. Phosphoric acid and boric acid solutions were mixed, heated to 260°C and stirred continuously to obtain a white slurry precursor. The obtained precursor was calcined at 300°C in a muffle furnace for 24 hours, and the obtained material was ground into a uniform powder, namely BPO4 powder. 0.4g of BPO4 powder was added to water, mixed with 1.0g of NbSi by ball milling for 8 hours, and dried to obtain a proton conductor, recorded as NbBPSi.
[0029] 2) The prepared proton conductor NbBPSi was mixed with a polyimide solution (mass fraction 2.5%), the mass ratio of the proton conductor to the polyimide being 1:10, the obtained mixture was ultrasonically treated for 3 hours to obtain a membrane-forming solution, the membrane-forming solution was placed on a glass plate, and kept in an oven at 60° C. for 12 to 60 hours to obtain a membrane material.
[0030] 3) Soaking in phosphoric acid to obtain a phosphoric acid-doped composite proton exchange membrane. The obtained membrane material was soaked in phosphoric acid at 80°C for 3 days to obtain a composite proton exchange membrane PA-NbBPSi-PI. The basic physical properties of the membrane were measured and shown in Table 1.
[0031] Comparative Example 1
[0032] Polyimide solution (mass fraction 2.5%) was used as a membrane-forming liquid, placed on a glass plate, and kept in an oven at 60°C for 12 to 60 hours to obtain a membrane material. The obtained membrane material was immersed in phosphoric acid at 80°C for 3 days to obtain PA-PI. The basic physical properties of the membrane were measured and shown in Table 1.
[0033] Example 2
[0034] 1) Niobium pentoxide (0.6 mmol) and hydrofluoric acid (40% by mass, 4 ml) are mixed, heated to 140°C and stirred continuously until dissolved, and ammonia water is added to adjust the pH to 6; 10 ml of 1 mol / L aqueous iodic acid solution is added, sealed, and statically treated at 180°C for 48 hours; the obtained product is filtered, washed, dried, calcined at 600°C for 4 hours, and ground into a uniform powder to obtain iodine niobium oxide HNbO(IO3)4. 1 g of iodine niobium oxide HNbO(IO3)4 is added to water, stirred evenly, and then 15 g of butyl titanate TEOS and 3 g of surfactant F127 are added, and stirring is continued for 30 minutes, sealed, and statically treated at 140°C for 6 hours; the obtained product is filtered, washed, dried, calcined at 500°C for 6 hours to obtain a mixture of iodine niobium oxide HNbO(IO3)4 and titanium dioxide TiO2, which is recorded as NbTi. Phosphoric acid and boric acid solutions were mixed, heated to 220°C and stirred continuously to obtain a white slurry precursor. The obtained precursor was calcined at 600°C in a muffle furnace for 2 hours, and the obtained material was ground into a uniform powder, namely BPO4 powder. 0.4g of BPO4 powder was added to water, mixed with 1.0g of NbTi by ball milling for 8 hours, and dried to obtain a proton conductor, recorded as NbBPTi.
[0035] 2) The prepared proton conductor NbBPTi was mixed with a polysulfone solution (mass fraction 2.5%), the mass ratio of the proton conductor NbBPTi to the polysulfone was 1:15, the obtained mixture was ultrasonically treated for 3 hours to obtain a membrane-forming solution, the membrane-forming solution was placed on a glass plate, and kept in an oven at 60° C. for 12 to 60 hours to obtain a membrane material.
[0036] 3) Soaking in phosphoric acid to obtain a composite proton exchange membrane doped with phosphoric acid. The obtained membrane material was soaked in phosphoric acid at 60°C for 4 days to obtain a composite proton exchange membrane PA-NbBPTi-PSF. The basic physical properties of the membrane were measured and shown in Table 1.
[0037] Comparative Example 2
[0038] Polysulfone solution (mass fraction 2.5%) was used as a membrane-forming liquid, placed on a glass plate, and kept in an oven at 60°C for 12 to 60 hours to obtain a membrane material. The obtained membrane material was immersed in phosphoric acid at 60°C for 4 days to obtain PA-PSF. The basic physical properties of the membrane were measured and shown in Table 1.
[0039] Example 3
[0040] 1) Niobium pentoxide (0.6 mmol) and hydrofluoric acid (40% by mass, 4 ml) are mixed, heated to 120°C and stirred continuously until dissolved, and ammonia water is added to adjust the pH to 6; 10 ml of 1 mol / L iodic acid aqueous solution is added, sealed, and statically treated at 160°C for 72 hours; the obtained product is filtered, washed, dried, calcined at 400°C for 12 hours, and ground into a uniform powder to obtain iodine niobium oxide HNbO(IO3)4. 1 g of iodine niobium oxide HNbO(IO3)4 is added to water, stirred evenly, and then 10 g of ethyl orthosilicate, 5 g of ethyl zirconate and 3 g of surfactant CTAB are added, stirring is continued for 30 minutes, sealed, and statically treated at 80°C for 18 hours; the obtained product is filtered, washed, dried, calcined at 600°C for 6 hours to obtain a mixture of iodine niobium oxide HNbO(IO3)4, silicon dioxide SiO2 and zirconium dioxide ZrO2, which is recorded as NbSiZr. Phosphoric acid and boric acid solutions were mixed, heated to 280°C and stirred continuously to obtain a white slurry precursor; the obtained precursor was calcined at 300°C in a muffle furnace for 24 hours, and the obtained material was ground into a uniform powder, namely BPO4 powder. 0.4g of BPO4 powder was added to water, mixed with 1.0g of NbSiZr by ball milling for 8 hours, and dried to obtain a proton conductor, recorded as NbBPSiZr.
[0041] 2) The prepared proton conductor NbBPSiZr was mixed with a polybenzimidazole solution (mass fraction 2.5%), the mass ratio of the proton conductor to the polybenzimidazole being 1:5, the obtained mixture was ultrasonically treated for 3 hours to obtain a membrane-forming solution, the membrane-forming solution was placed on a glass plate, and kept in an oven at 60° C. for 12 to 60 hours to obtain a membrane material.
[0042] 3) The obtained membrane material was immersed in phosphoric acid at 100° C. for 2 days to obtain a composite proton exchange membrane PA-NbBPSiZr-PBI. The basic physical properties of the membrane were measured and shown in Table 1.
[0043] Comparative Example 3
[0044] 1) Niobium pentoxide (0.6 mmol) and hydrofluoric acid (mass fraction 40%, 4 ml) are mixed, heated to 120° C. and stirred continuously until dissolved, and ammonia water is added to adjust the pH to 6; 10 ml of 1 mol / L iodic acid aqueous solution is added, sealed, and statically treated at 160° C. for 72 hours; the obtained product is filtered, washed, dried, calcined at 400° C. for 12 hours, and ground into a uniform powder to obtain iodinated niobium HNbO(IO3)4; 1 g of iodinated niobium HNbO(IO3)4 is added to water, stirred evenly, and then 10 g of ethyl orthosilicate, 5 g of ethyl zirconate and 3 g of surfactant CTAB are added, stirring is continued for 30 minutes, sealed, and statically treated at 80° C. for 18 hours; the obtained product is filtered, washed, dried, calcined at 600° C. for 6 hours to obtain a mixture of iodinated niobium HNbO(IO3)4, silicon dioxide SiO2 and zirconium dioxide ZrO2, which is recorded as NbSiZr.
[0045] 2) The prepared NbSiZr was mixed with a polybenzimidazole solution (mass fraction 2.5%), the mass ratio of NbSiZr to polybenzimidazole was 1:5, the obtained mixture was ultrasonically treated for 3 hours to obtain a film-forming solution, the film-forming solution was placed on a glass plate, and kept in an oven at 60° C. for 12 to 60 hours to obtain a membrane material.
[0046] 3) The obtained membrane material was immersed in phosphoric acid at 100° C. for 2 days to obtain a composite proton exchange membrane PA-NbSiZr-PBI. The basic physical properties of the membrane were measured and shown in Table 1.
[0047] Comparative Example 4
[0048] 1) Mix niobium pentoxide (0.6mmol) and hydrofluoric acid (mass fraction 40%, 4ml), heat to 120℃ and stir continuously until dissolved, add ammonia water to adjust pH to 6; add 10ml of 1mol / L iodic acid aqueous solution, seal, and statically treat at 160℃ for 72 hours; the obtained product is filtered, washed, dried, calcined at 400℃ for 12 hours, and ground into a uniform powder to obtain iodine niobium HNbO(IO3)4. Phosphoric acid and boric acid solutions are mixed, heated to 280℃ and stirred continuously to finally obtain a white slurry precursor; the obtained precursor is calcined at high temperature in a muffle furnace, and the obtained material is ground into a uniform powder, namely BPO4 powder. 0.4g BPO4 powder is added to water, mixed with 1.0g iodine niobium HNbO(IO3)4 powder by ball milling for 8 hours, and dried to obtain a mixture of iodine niobium HNbO(IO3)4 and boron phosphate BPO4, recorded as NbBP.
[0049] 2) The prepared NbBP was mixed with a polybenzimidazole solution (mass fraction 2.5%), the mass ratio of NbBP to polybenzimidazole was 1:5, the obtained mixture was ultrasonically treated for 3 hours to obtain a membrane-forming solution, the membrane-forming solution was placed on a glass plate, and kept in an oven at 60° C. for 12 to 60 hours to obtain a membrane material.
[0050] 3) The obtained membrane material was immersed in phosphoric acid at 100°C for 2 days to obtain an organic-inorganic composite medium- and high-temperature proton exchange membrane PA-NbBP-PBI. The basic physical properties of the membrane were measured and shown in Table 1.
[0051] Comparative Example 5
[0052] Polybenzimidazole solution (mass fraction 2.5%) was used as a membrane-forming liquid, placed on a glass plate, and kept in an oven at 60°C for 12 to 60 hours to obtain a membrane material. The obtained membrane material was immersed in phosphoric acid at 100°C for 2 days to obtain PA-PBI. The basic physical properties of the membrane were measured and shown in Table 1.
[0053] Compared with Example 3, in Comparative Example 3, except that the proton conductor NbSiZr does not contain BPO4, the other compositions and parameters are the same; in Comparative Example 4, except that the proton conductor NbBP does not contain inorganic oxides SiO2 and ZrO2, the other compositions and parameters are the same. By comparing Example 3 with Comparative Example 3 and Comparative Example 4, it can be seen that the boron phosphate and inorganic oxide in the proton conductor of the present invention play an important role in improving the conductivity and phosphoric acid retention rate of the composite membrane. Nanoscale inorganic oxides can provide abundant surface area, act as carriers and skeletons, and have strong interactions with iodine niobium oxide HNbO(IO3)4, which can enrich the hydrogen bond network and promote proton conduction. In addition, the introduction of BPO4 further improves the proton conduction performance of the composite material. Therefore, in the present invention, iodine niobium oxide HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2 work synergistically to jointly improve the conductivity of the material. At the same time, the inorganic oxide crystals in the proton conductor of the present invention have a smaller size and a larger specific surface area, and are better water-retaining and acid-retaining materials, making an important contribution to improving the phosphoric acid retention rate.
[0054] The above are only some embodiments of the invention, and do not limit the present invention in any form. All raw material ratios, upper and lower limits of working conditions and interval values in the preparation process of the present invention can realize the present invention, and the embodiments are not listed one by one here. Any person familiar with this profession, without departing from the technical solution of the present invention, when using the above technical content to make some changes or modifications to an equivalent embodiment of decorating, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still belongs to the scope of the technical solution of the present invention.
[0055] Table 1
[0056]
Claims
1. A composite proton exchange membrane, characterized in that: The composite proton exchange membrane is composed of a proton conductor, a polymer matrix and phosphoric acid, and the proton conductor is composed of iodinated niobium HNbO(IO3)4, boron phosphate BPO4 and inorganic oxide MO2.
2. A composite proton exchange membrane according to claim 1, characterized in that: The inorganic oxide MO2 is one or two of SiO2, TiO2 or ZrO2, and the crystal size of the inorganic oxide MO2 is 100-500nm; the mass ratio of the iodinated niobium HNbO(IO3)4 to the inorganic oxide MO2 is 1:(2-15); the mass ratio of the boron phosphate BPO4 to the sum of the iodinated niobium HNbO(IO3)4 and the inorganic oxide MO2 is 1:(2.5-25).
3. A composite proton exchange membrane according to claim 1, characterized in that: The polymer matrix includes one of polysulfone, polyetheretherketone, polyimide, polybenzimidazole and polyphenylene sulfide sulfone.
4. A composite proton exchange membrane according to claim 1, characterized in that: The mass ratio of the proton conductor to the polymer matrix is 1:(5-20).
5. A method for preparing a composite proton exchange membrane according to any one of claims 1 to 4, characterized in that: The steps include: (1) mixing niobium pentoxide and hydrofluoric acid, heating to 100-140° C. to dissolve, adding ammonia water to adjust the pH to 5-7, adding iodic acid, sealing, and statically treating at 150-180° C. for 48-72 hours; filtering, washing, drying, and calcining at 400-600° C. for 4-12 hours to obtain iodinated niobium HNbO(IO3)4; The iodinated niobium HNbO(IO3)4, an inorganic oxide precursor and a surfactant are mixed, stirred for 30 to 60 minutes, sealed, and statically treated at 80 to 140°C for 6 to 18 hours; the obtained product is filtered, washed, dried, and calcined at 400 to 600°C for 6 to 18 hours to obtain a mixture of iodinated niobium HNbO(IO3)4 and an inorganic oxide MO2, which is recorded as NbM; The phosphoric acid and boric acid solutions are mixed and heated to 220-280° C. to obtain a boron phosphate precursor; the boron phosphate precursor is calcined at high temperature to obtain boron phosphate BPO4; Mixing boron phosphate BPO4 and NbM by ball milling to obtain the proton conductor; (2) mixing the proton conductor with a polymer matrix solution to form a membrane; (3) The membrane is immersed in phosphoric acid to obtain a composite proton exchange membrane.
6. The preparation method according to claim 5, characterized in that: The temperature of high-temperature calcination of the boron phosphate precursor is 300-600° C., and the time is 2-24 hours.
7. The preparation method according to claim 5, characterized in that: The inorganic oxide precursor includes one or two of tetraethyl orthosilicate, ethyl titanate, butyl titanate, tetraethoxysilane, and ethyl zirconate, the surfactant includes any one of F127, P123, and CTAB, and the mass ratio of the inorganic oxide precursor to the surfactant is (5-15):
3.
8. The preparation method according to claim 5, characterized in that: In step (2), the proton conductor and the polymer matrix solution are formed into a film by a casting method.
9. The preparation method according to claim 5, characterized in that: The proton conductor is mixed with a polymer matrix solution to obtain a mixture, the mixture is ultrasonically treated for 2 to 4 hours to obtain a membrane-forming solution, the membrane-forming solution is placed on a glass plate, and dried at 55 to 65° C. to obtain the membrane; in the step (3), the membrane is immersed in phosphoric acid at a temperature of 60 to 100° C. and a soaking time of 2 to 4 days; the concentration of the polymer matrix solution is 2.5 to 5% by mass.
10. Use of the composite proton exchange membrane according to any one of claims 1 to 4 or the composite proton exchange membrane prepared by the preparation method according to any one of claims 5 to 9, characterized in that: Applied in fuel cells, the applicable temperature is 100-200℃.
Citation Information
Patent Citations
Method for preparation of organic-inorganic composite type proton exchanging membrane used for high-temperature fuel cell
CN101207213A
Method for producing high-temperature proton exchange membrane
CN107808969A